Mycobacterium tuberculosis PE9 protein has high activity binding peptides which inhibit target cell invasion (2016)
PE/PPE proteins are involved in several processes during Mycobacterium tuberculosis (Mtb) infection of target cells; studying them is extremely interesting as they are the only ones from the Mycobacterium genus, they abound in pathogenic species such as Mtb and their function remains yet unknown. The PE9 protein (Rv1088) was characterised, the rv1088 gene was identified by PCR in Mtb complex strains and its expression and localisation on mycobacterial surface was confirmed by Western blot and immunoelectron microscopy. Bioinformatics tools were used for predicting PE9 protein structural aspects and experimental study involved the circular dichroism of synthetic peptides. The peptides were tested in binding assays involving U937 and A549 cells; two high activity binding peptides (HABPs) were found for both cell lines (39226-1MSYMIATPAALTAAATDIDGI21 and 39232-125YQRHFGTGGQPEFRQHSEHRR144), one for U937 (39231-104YAGAGRRQRRRRSGDGQWRLRQ124) and one for A549 (39230-83YGTGVFRRRRGRQTVTAAEHRA103). HABP 39232 inhibited mycobacterial entry to A549 cells (~70%) and U937 cells (~50%), peptides 39226 and 39231 inhibited entry to U937 cells (~60% and 80%, respectively) and peptide 39230 inhibited entry to A549 cells (~60%). This emphasised HABPs' functional importance in recognition between Mtb H37Rv and target cell receptors. These peptide sequences could be involved in invasion and were recognised by the host's immune system, thereby highlighting their use when designing an efficient anti-tuberculosis multiantigenic vaccine. © 2016 Elsevier B.V.